A multi-missile cooperative coverage guidance strategy based on the ISO algorithm - Hua, Ziqing; Wei, Mingying; Li, Yunqian; Cui, Zhengda (Journal of physics. Conference series, 2025)
In long-range air defense multi-missile cooperative interception missions, due to the low accuracy of indication information and the lack of ground radar support, significant errors exist in estimating the true position of the target. This makes it difficult for the interception regions of multiple missiles to cooperatively cover the target error region. To address this issue, a multi-missile cooperative coverage guidance strategy based on an improved snake optimization (ISO) algorithm is proposed. First, a missile cooperative coverage model is established, with the interception regions treated as nodes in the coverage optimization problem, and the highest regional interception probability used as the optimization criterion. Next, the snake optimization (SO) algorithm is improved by enhancing its initialization, exploration, and exploitation phases, resulting in the ISO algorithm. Based on this, a multi-missile cooperative coverage guidance strategy is proposed, where the interception regions of each missile are optimally allocated within the target error region, expanding the overall interception region and improving the cooperative interception probability across the coverage area. Finally, the effectiveness of the proposed strategy is validated through numerical simulations.